1999
DOI: 10.1136/jme.25.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Genetic privacy: orthodoxy or oxymoron?

Abstract: In this paper we question whether the concept of "genetic privacy" is a contradiction in terms. And, if so, whether the implications of such a conclusion inevitably impact on how society comes to perceive privacy and responsibility generally. Current law and ethical discourse place a high value on self-determination and the rights of individuals. In the medical sphere, the recognition ofpatient "rights" has resulted in health professionals being given clear duties of candour andfrankness. Dilemmas arise, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 4 publications
0
22
0
1
Order By: Relevance
“…56 A recent analysis of the current legal situation in USA has also concluded that professionals should encourage but not coerce the sharing of important health risk information by genetic counselling clients with their at-risk relatives. 57 It has been argued that genetic information cannot by its very nature be private and should therefore not be bound by the usual professional codes of respect for confidentiality 15 -with genetic information generated about one individual being treated as essentially familial and therefore to be shared with other family members on a 'joint account' model 58 -although, of course, a case can also be made for genetic information being regarded as the most private information of all. 59 While we all have moral obligations to our kin, not all such obligations are enforced by health professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 A recent analysis of the current legal situation in USA has also concluded that professionals should encourage but not coerce the sharing of important health risk information by genetic counselling clients with their at-risk relatives. 57 It has been argued that genetic information cannot by its very nature be private and should therefore not be bound by the usual professional codes of respect for confidentiality 15 -with genetic information generated about one individual being treated as essentially familial and therefore to be shared with other family members on a 'joint account' model 58 -although, of course, a case can also be made for genetic information being regarded as the most private information of all. 59 While we all have moral obligations to our kin, not all such obligations are enforced by health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…6,9,10,12 Nondirectiveness has long been held to be a central principle of genetic counselling, 13 despite doubts about whether this is always possible in practice 14 or appropriate to all genetic counselling situations. 15 While disclosure without consent would violate the client's privacy, 16 any steps taken to persuade or encourage a counsellee to disclose information to another family member would clearly amount to directive counselling.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the confirmation of hereditary cancer in the family often involves duties to confer information about heredity to other family members, concerns related to the disclosure of the information, and worries for other family members Meiser, 2005;Sommerville and English, 1999;Wilson et al, 2004). Nine out of ten individuals who have undergone genetic testing for HNPCC are satisfied with their decision, but 59% still state that the test result had a significant psychosocial impact on their life (Esplen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…10 Others, however, have come down in favour of a broader duty of care including other family members in addition to the patient. 11 The Human…”
Section: Guidelines On Confidentialitymentioning
confidence: 99%